Forest Health Status in North America - Borys Tkacz; Ben Moody; Jaime Villa Castillo (The Scientific World Journal)
The forests of North America provide a variety of benefits including water, recreation, wildlife habitat, timber, and other forest products. However, they continue to face many biotic and abiotic stressors including fires, native and invasive pests, fragmentation, and air pollution. Forest health specialists have been monitoring the health of forests for many years. This paper highlights some of the most damaging forest stressors affecting North American forests in recent years and provides some projections of future risks.